PENDAMPINGAN PENINGKATAN KOMPETENSI KOMUNITAS PENGELOLA JURNAL LPTNU PCNU NGANJUK MENUJU JURNAL NASIONAL TERAKREDITASI - Edi Nurhidin (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
This study focuses on mentoring strategies for Nganjuk Regency LPTNU PCNU journal managers. This strategy has two main orientations: increasing the competence of journal managers and accrediting the journals being managed. This study uses the participatory action research (PAR) method because both orientations are forms of fundamental social transformation. This study found that the management of the journal "Kartika: Journal of Islamic Studies," published by LPTNU PCNU Nganjuk Regency, had two fundamental problems: understanding journal management according to national journal quality standards and lack of budget. These two issues are the basis for planning mentoring programs for servants and service partners, so the program design is a workshop and follow-up in the form of mentoring. This fact has implications for the meaning of the concept of service, which does not only stop at planning and implementing the program but makes the program the basis for follow-up so that the service carried out can become more substantive so that fundamental transformation and independence can occur, not superficial service.